Tracking large solid constructs suspended in a rotating bioreactor: A combined experimental and theoretical study. - Cummings, L; Sawyer, N; Morgan, S; Rose, F; Waters, S (2009)
We present a combined experimental and theoretical study of the trajectory of a large solid cylindrical disc suspended within a fluid-filled rotating cylindrical vessel. The experimental set-up is relevant to tissue-engineering applications where a disc-shaped porous scaffold is seeded with cells to be cultured, placed within a bioreactor filled with nutrient-rich culture medium, which is then rotated in a vertical plane to keep the growing tissue construct suspended in a state of "free fall." The experimental results are compared with theoretical predictions based on the model of Cummings and Waters (2007), who showed that the suspended disc executes a periodic motion. For anticlockwise vessel rotation three regimes were identified: (i) disc remains suspended at a fixed position on the right-hand side of the bioreactor; (ii) disc executes a periodic oscillatory motion on the right-hand side of the bioreactor; and (iii) disc orbits the bioreactor. All three regimes are captured experimentally, and good agreement between theory and experiment is obtained. For the tissue engineering application, computation of the fluid dynamics allows the nutrient concentration field surrounding a tissue construct (a property that cannot be measured experimentally) to be determined (Cummings and Waters, 2007). The implications for experimental cell-culture protocols are discussed.